Pengembangan Media Pembelajaran “Fruit Game’s” Interaktif untuk Meningkatkan Kemampuan Kognitif Pada Anak Usia Dini - Nur Nabila; Veryawan Veryawan; Nur Balqis Mutia (Jurnal Raudhah, 2026)
The use of learning media in early childhood education is still limited and tends to be traditional in approach, making it less appealing to children. This situation results in the cognitive development of early childhood not reaching its maximum potential due to the lack of interactive and enjoyable learning tools. This study aims to develop an interactive game media called “Fruit Game's” to improve the cognitive development of early childhood. The type of research used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research was conducted at Al-Azhar Kindergarten with subjects aged 4-5 years. The data collection instruments were interviews and validation questionnaires from media experts, subject matter experts, and language experts. The interactive “Fruit Game's” media was declared suitable for use based on the experts' assessment, and media users can improve children's cognitive abilities in recognizing colors, shapes, and simple counting concepts. Interactive educational game learning media is recommended for early childhood teachers as an innovative learning medium to improve the cognitive abilities of early childhood.